Neuropathic Pain Intensity, Unpleasantness, Coping Strategies, and Psychosocial Factors after Spinal Cord Injury: An Exploratory Longitudinal Study During the First Year - Taylor, Julian; Huelbes, Silvia; Albu, Sergiu; Gómez-Soriano, Julio; Peñacoba, Cecilia; Poole, Helen M. (Pain medicine (Malden, Mass.), 2012)
Objective.  To determine the temporal relationship between pain‐related coping strategies and psychosocial factors with non‐evoked neuropathic pain (NP) intensity and unpleasantness in patients during the subacute phase of spinal cord injury (SCI). Design.  Exploratory longitudinal study of NP from 2 to 12 months. Setting.  Hospital Nacional de Parapléjicos, Toledo, Spain. Subjects.  A maximum of 26 patients with early symptoms of NP after SCI with a neurological level above the Th10 spinal level. Outcome Measures.  Multidimensional Pain Inventory‐Spinal Cord Injury Version, Coping Strategies Questionnaire, General 7‐day pain intensity and unpleasantness rated with a visual analog scale, Spearman correlation analysis. Results.  Pain‐related coping strategies and psychosocial factors remained stable from 2 to 12 months after SCI. Initially pain intensity and unpleasantness were rated independently, but at 6 months were intercorrelated along with “pain severity,”“life interference,” and “catastrophizing.”“Coping self‐statements” and “solicitous responses from others” were frequently adopted, compared with “ignoring pain sensations” and “catastrophising.” Perception of “pain severity” correlated with “support,”“solicitous responses from others,”“distracting responses from others,” and “life control” at 6 months, while pain intensity and unpleasantness were related to “coping self‐statements,”“catastrophizing,”“distancing from pain,” and “praying.” Conclusions.  Pilot longitudinal data suggest that pain‐related coping strategies are adopted early after subacute SCI, and correlate with both pain intensity and unpleasantness. Future longitudinal studies of SCI with sufficient sample size will be instrumental to determine the causal relationship between psychosocial factors and coping strategies on pain.